Μ-conotoxin TsIIIA, a peptide inhibitor of human voltage-gated sodium channel hNav1.8. (30th October 2020) - Yang, Manyi; Zhou, Maojun
Abstract: TsIIIA, the first μ-conotoxin from Conus tessulatus, can selectively inhibit rat tetrodotoxin-resistant sodium channels. TsIIIA also shows potent analgesic activity in a mice hotplate analgesic assay, but its effect on human sodium channels remains unknown. In this study, eight human sodium channel subtypes, hNav 1.1- hNav 1.8, were expressed in HEK293 or ND7/23 cells and tested on the chemically synthesized TsIIIA. Patch clamp experiments showed that 10 μM TsIIIA had no effects on the tetrodotoxin-sensitive hNav 1.1, hNav 1.2, hNav 1.3, hNav 1.4, hNav 1.6 and hNav 1.7, as well as tetrodotoxin-resistant hNav 1.5. For tetrodotoxin-resistant hNav 1.8, concentrations of 1, 5 and 10 μM TsIIIA reduced the hNav 1.8 currents to 59.26%, 36.21% and 24.93% respectively. Further detailed dose-effect experiments showed that TsIIIA inhibited hNav 1.8 currents with an IC50 value of 2.11 μM. In addition, 2 μM TsIIIA did not induce a shift in the current–voltage relationship of hNav 1.8. Taken together, the hNav 1.8 peptide inhibitor TsIIIA provides a pharmacological probe for sodium channels and a potential therapeutic agent for pain. Highlights: Conotoxin TsIIIA with three disulfide bonds was chemically synthesized. 10 μmol TsIIIA has no effects on human voltage-gated sodium channel 1.1–1.7 TsIIIA inhibits human voltage-gated sodium channel 1.8 The half inhibition concentration of TsIIIA on sodium channel 1.8 is 2.1 μmol. TsIIIA does not change the current-voltage relationships of sodium channel 1.8